A systematic review of the worldwide prevalence of survivors of poliomyelitis reported in 31 studies - Alice Theadom; Shivanthi Balalla; Kelly M Jones; Valery L Feigin; Gordon Jackman (BMJ Open)
Background Accurate prevalence figures estimating the number of survivors of poliomyelitis (disease causing acute flaccid paralysis) following poliovirus infection are not available. We aim to undertake a systematic review of all literature concerning the prevalence of survivors of poliomyelitis.Methods Electronic databases were searched from 1900 up to May 2016 for peer-reviewed studies using a population-based approach witha defined denominator and some form of diagnostic or clinical verification of polio. Exclusion criteria were any prevalence data that were unable to be extracted or calculated and studies reporting on incidence only. The quality of each included study was assessed using an existing tool modified for use in prevalence studies. Average crude prevalence rates were used to calculate worldwide estimates.Results Thirty-one studies met criteria with 90% of studies conducted in low-income to lower middle-income countries. Significant variability in the prevalence of survivors of poliomyelitis was revealed, in low- income to lower middle-income (15 per 100 000 in Nigeria to 1733 in India) and upper-middle to high-income countries (24 (Japan) to 380 per 100 000 (Brazil). The total combined prevalence of survivors of poliomyelitis for those studies at low to moderate risk of bias ranged from 165 (high-income countries) to 425 (low-income to lower middle-income countries) per 100 000 person-years. Historical lameness surveys of children predominated, with wide variation in case definition and assessment criteria, and limited relevance to current prevalence given the lack of incidence of poliovirus infection in the ensuing years.Conclusions These results highlight the need for future epidemiological studies of poliomyelitis to examine nationally representative samples, including all ages and greater focus on high-income countries. Such efforts will improve capacity to provide reliable and more robust worldwide prevalence estimates.